Estrone and Estradiol Levels in Breast Cancer Patients Using Anastrozole Are Not Related to Body Mass Index - Coscia, Eduardo Borges; Sabha, Maricene; Gerenutti, Marli; Groppo, Francisco Carlos; Bergamaschi, Cristiane de Cássia (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Objective Obesity is associated with an increased risk for breast cancer. Recent studies have shown that aromatase inhibitors may be less effective in women with a high body mass index (BMI). The aim of this study was to establish the relationship between the BMI and plasma estrone and estradiol levels in postmenopausal women with hormone receptor-positive breast cancer using anastrozole.Methods In this cohort study, the patients were divided into three groups according to BMI (normal weight, overweight and obese) to compare and correlate plasma hormone levels before starting anastrozole hormone therapy and three months after treatment. Plasma hormone levels were compared for age and use of chemotherapy.Results A statistically significant reduction in estrone and estradiol levels was observed between baseline and three months after starting the anastrozole treatment (p < 0.05). There was no statistically significant difference in plasma estrone and estradiol levels among the BMI groups (p > 0.05), but a significant reduction in plasma estrone levels was observed after three-months' treatment relative to baseline in all groups, as well as a reduction in estradiol in the obese group (p < 0.05). The use of chemotherapy and age > 65 years had no influence on plasma steroid levels.Conclusion Changes in estrone and estradiol levels in the studied groups were not associated with BMI, chemotherapy or age.
Keywords: breast neoplasms; estrone; estradiol; body mass index; anastrozole